Effects of disruption of xylanase-encoding genes on the xylanolytic system of Streptomyces lividans. - Arhin, F F (1994)
Wild-type Streptomyces lividans produced the three xylanases (XlnA, XlnB, and XlnC) when xylan, xylan hydrolysates obtained by the action of XlnA, XlnB, and XlnC, or purified small xylo-oligosaccharides (xylobiose [X2], xylotriose [X3], xylotetraose [X4], and xylopentaose [X5]) were used as the carbon source. The three xylanase genes of S. lividans (xlnA, xlnB, and xlnC) were disrupted by using vectors that integrate into the respective genes. Disruption of one or more of the xln genes resulted in reduced growth rates and reduced total xylanase activities when the strain was grown in xylan. The greatest effect was observed when xlnA was disrupted. In medium containing xylan, disruption of xlnA did not affect expression of xlnB and xlnC; disruption of xlnB did not affect expression of xlnA but affected expression of xlnC; and disruption of xlnC did not affect expression of xlnA but affected expression of xlnB. A fraction of XlnB or XlnC hydrolytic products (those with a degree of polymerization greater than 11 [X11]) was found to stimulate expression of xlnB and xlnC in strains disrupted in xlnC and xlnB, respectively, whereas lower-molecular-weight fractions as well as purified small xylo-oligosaccharides did not. The stimulating molecule(s) lost its effect when it was hydrolyzed further by XlnA. A mechanism of transglycosylation reactions by the S. lividans xylanases is postulated to be involved in the regulation of xln genes.